Factors affecting the behavior of consumers in Iloilo City towards Fintech during the Covid-19 pandemic - Agupita, Leonardo P.; Malihan, Jones Jasper I. (2024.)
Financial Technology (FinTech) has been around in recent years yet developing countries still do not have a strong infrastructure to stimulate and support consumer adoption. Despite the increasing categories available in the market, some consumers simply are not aware of these services (Tapanainen, 2020; Huong et al., 2021). Using the foundations of the Technology Acceptance Model (TAM) of Davis et al. (1989) as basis for the conceptual framework use, this study aims to determine the factors affecting the usage of FinTech consumers in Iloilo City during the COVID-19 pandemic. The researchers conducted the survey online due to physical limitations. Using descriptive research design, quantitative data, and convenience sampling method, 204 respondents have participated. These respondents are: a) Resident of Iloilo city during the administration of the online survey; b) They should have used at least one FinTech service during the pandemic, and c) They must be at least 18 years old by the time they answer the survey. The respondents' demographic variables are analyzed using the Pearson Chi-Square Test, to see any significant associations with their FinTech sage. While factors such as perceived risks of COVID-19 pandemic: perceived trust, perceived data protection, perceived data protection, perceived usefulness, and perceived ease of use were analyzed using Spearman Rho Correlation to determine their effect on FinTech usage. This study found that perceived data protection, perceived usefulness, and perceived ease of use affect the FnTech usage of consumers in Iloilo City during the COVID-19 pandemic. On the other hand, perceived risks of COVID-19 pandemic and perceived trust do not affect the respondents' FinTech usage.
Thesis (BSBA-Marketing). -- [Iloilo City] : University of the Philippines Visayas - College of Management, June 2022.